Exploring the historical origin of trigonometric function: Explorando el origen histórico de las funciones trigonométricas - Bendersky Vieyra, Estefanía Micol (2026)
This paper describes, based on various bibliographic sources, the mathematical developments that led to the construction of the mathematical object known as trigonometric functions throughout history. First, it addresses the emergence of trigonometric ratios. It then develops the construction of the notion of a function to visualize the framework within which different civilizations interpreted the object in question. Subsequently, it details the contributions to the construction of trigonometric functions from India. It also analyzes why the Arabs were interested in developing trigonometry during their time, without losing sight of the influence of spherical geometry and series in the consolidation of this mathematical object.